Children, care time, career priority – What matters for junior scientists' productivity and career perspective during the COVID-19 pandemic? - Muschalla, Beate; Sondhof, Anke; Wrobel, Ulrike (Work, 2022)
Background: The coronavirus (COVID-19) pandemic brought about restrictions, additional workload, insecurity, or need for inventing new routines for professionals worldwide. The pandemic and its restrictions have been discussed as a career shock. OBJECTIVE: Adding knowledge to this, our study investigated the academic and family (care) situation of young scientists in a German technical university. METHODS: We conducted an online survey including young scientists from a technical university in Germany in April 2021. 346 participants (mean age 33 years, 37% women) gave self-ratings on academic and life situation during the pandemic year, care work, preferences for scientific career and family life. RESULTS: Family and career were independent priorities (r = 0.021, p = 0.676). Two thirds (68%) of the young scientists reported no deterioration in scientific outcome during the pandefmic year. But, care times and number of children impacted negatively on scientific productivity in terms of publications. This was true for both women and men. CONCLUSIONS: Young scientists need individual support for their career perspective, according to their concrete career level and life situation.